Is clinical, musculoskeletal pain associated with poorer logical reasoning? - Helena Gunnarsson (PAIN Reports, 2021)
Abstract. Introduction:. It has been hypothesized that pain disrupts system 2 processes (eg, working memory) presumed to underlie logical reasoning. A recent study examining the impact of experimentally induced pain on logical reasoning found no evidence of an effect. Objectives:. The aim of this study was to examine whether clinical pain, which is qualitatively different from experimental pain, would lower the ability to reason logically. Methods:. Ninety-six participants completed a questionnaire containing 3 different logical reasoning tasks (the cognitive reflection test, the belief bias syllogisms task, and the conditional inference task), questions about pain variables (present pain intensity, pain intensity during the last 24 hours, the influence of pain on daily activities, pain duration, and pain persistence), questions about other pain-related states (anxiety, depression, and fatigue), and pain-relieving medication. Correlations between the logical reasoning tasks and the pain variables were calculated. Results:. For 2 of the 3 logical reasoning tasks (the cognitive reflection test and the belief bias syllogisms task), clinical pain was unrelated to logical reasoning. Performance on context-free logical reasoning showed a significant negative correlation with present pain intensity, but not with the other pain variables. Conclusion:. This finding that logical reasoning ability is largely unrelated to clinical pain is highly consistent with previous research on experimentally induced pain. Pain should probably not constitute a significant barrier to logical reasoning in everyday life.